Design and Measurement Characterization of Two 300 GHz Fan-In Antennas in Package for Upcoming Sub-THz Applications - Pfahler, Tim; Vossiek, Martin (2024 54th European Microwave Conference, EuMC 2024, 2024)
This paper presents the design and measurement characterization of two antennas in package (AiP) feeding concepts in the chip's fan-in wafer level ball grid array (WLB) at 300 GHz. The key advantage of the two designs is the vertical integration of the AiPs, directly above the integrated circuit (IC), instead of lateral antenna placement as in fan-out WLB. This minimizes the separation of package and IC components, resulting in minimal insertion loss (IL) at the IC to package transition. A probe-feed AiP, using a through-mold-via (TMV), and an electro-magnetic (EM) coupled AiP are presented and described in detail. Both AiPs are verified by measuring the return loss, the frequency-dependent antenna gain, and the radiation pattern. The measured -10 dB matching bandwidth of the probe-feed AiP and EM-coupled AiP is 36 GHz and 12 GHz, respectively. Furthermore, a laser scanning microscope was used to determine manufacturing tolerances and to account for deviations in the frequency response between measurement and simulation. A simulated antenna peak gain beyond 5.5 dBi emphasizes the underlying packaging approach to compensate for the free-space loss at 300 GHz for future sensing and communication systems in package applications.
CRIS-Team Scopus Importer:2024-12-13
Keywords: Antennas-in-package (AiP); fan-in WLB (wafer level ball grid array); system-in-package (SiP); wafer level packaging